Empowerment Women's Organizations In The Era Of Digitalization (Dharma Women's Unity in East Java Province, Indonesia) - Rapitasari, Diana; Pribadiyono, Pribadiyono; Suwitho, Suwitho (International Journal of Science, Technology & Management, 2024)
Era 4.0, digital change in almost all lines of activity, requires digitalization of development, organizational management can keep up with the times, administrators and members are required to follow technology and also apply it to organizational management, creating competent, globally competitive, competitive and innovative human resources (Setiawan, 2016). Previous research studies from primary and secondary data showed that the impact of digitalization was also felt by the East Java DWP by carrying out manual reporting which was not supported by good publications, resulting in all work activities achieved not being able to reach the maximum by the wider community, especially the people of East Java. Existence is able to come out of the existence of something and is able to transcend itself because the existence of a dynamic process comes from existere, which means coming out of, going beyond or overcoming, so existence is not rigid and stops but experiences development or decline depending on the ability to actualize its potential (Abidin, 2006). Women's empowerment accelerates economic growth in a country where to achieve development goals according to the concept of Development Economics, an appropriate development strategy is needed. Empowerment is one of the strategies most widely used in overcoming various development problems because without women's development, economic growth and development will not occur (Marditama et.al, 2021:11). Choosing an interpretive way of how individuals who experience it directly gives meaning to interactions that have been experienced in social life with a pattern of prioritizing a series of descriptions of the experiences of the informants, interpretive builds meaning from life experiences experienced directly (Cresswell, 2018). An interpretive approach to how the East Java DPD organization exists in the era of digitalization is the main focus of the study, how the subjects, namely women who are members of the East Java DWP organization, continue to exist amidst the onslaught of digitalization. Increasing the role of women in DWP so that they are ready in the 4.0 era and ready to face global challenges so that DWP members and families are able to develop their potential through DWP priority programs so that they are able to support the DWP organization to become a center of excellence in empowering women and families and can participate in progress world civilization. It is necessary to increase members' understanding of organizational management through a system that needs to be built in an integrated manner. By instilling a sense of belonging to the organization, caring and unity, a solid organization with creative and innovative activities will be formed.